Performance Analysis of Matrix Multiplication Algorithms Using MPI and OpenMP - Galstyan, Tigran M. (Mathematical Problems of Computer Science, 2021)
The combination of OpenMP and MPI in programming is called hybrid programming. Hybrid programming (through messages and shared memory) has gained an important role since the appearance of cluster architectures. A hybrid programming method combines the MPI and OpenMP libraries to use this hierarchical multi-core architecture. The purpose of this work is to carry out the performance analysis of matrix multiplication algorithms in a cluster system. Each node in the cluster consists of multiple core CPUs, in which memory is distributed among the nodes and shared memory. Algorithms use MPI as a message-passing mechanism and OpenMP as shared memory.